Alemtuzumab clearance, lymphocyte count, and T‐cell chimerism after hematopoietic stem cell transplant in sickle cell disease. Issue 1 (17th November 2021) - Furstenau, Dana; Peer, Cody J.; Hughes, Thomas E.; Uchida, Naoya; Tisdale, John; Hall, Oliver Morgan; Figg, William D.; Hsieh, Matthew
Abstract: Study Objective: Alemtuzumab is a monoclonal antibody that targets the cell surface antigen CD52 on lymphocytes. Although it is used for the treatment of hematologic malignancies, such as chronic lymphocytic leukemia, and incorporated into many hematopoietic stem cell transplant (HSCT) conditioning regimens, few studies have evaluated the pharmacology of alemtuzumab in adult patients with sickle cell disease (SCD). We therefore examined the pharmacokinetics (PK) and pharmacodynamics (PD) of alemtuzumab in adults with SCD who received a matched related donor HSCT to determine if the clearance of alemtuzumab affects transplant outcomes. Design: PK and PD analysis of patient data from a single‐center clinical trial. Setting: Clinical research center. Patients: Twenty‐two adult patients with SCD who received one of two nonmyeloablative allogeneic HSCT regimens: alemtuzumab and total body irradiation (Alem‐TBI) or pentostatin, cyclophosphamide, alemtuzumab, and total body irradiation (Pento‐Cy‐Alem‐TBI). Measurements and Main Results: Alemtuzumab serum concentrations, absolute lymphocyte counts, T‐cell (CD3), and myeloid (CD14/15) chimerism were collected at distinct time points and analyzed. A semi‐mechanistic PK population model was built to understand inter‐individual differences in pharmacology. Alemtuzumab was detectable up to 28 days post‐HSCT. The mean alemtuzumab level 7 days after transplant for patients on Alem‐TBI was 818 ng/ml, significantly lower than the mean level of 1502 ng/ml for patients on Pento‐Cy‐Alem‐TBI ( p  < 0.001), but this difference decreased as time progressed. The clearance of alemtuzumab was linear, and the half‐life was longer in the Pento‐Cy‐Alem‐TBI group (average half‐life = 61.1 h) compared to the Alem‐TBI group (average half‐life = 44.1 h) ( p  < 0.001). The CD3 chimerism at 2 and 4 months after transplant positively correlated with alemtuzumab levels collected on day 14 after transplant ( R 2  = 0.40 and p  = 0.004 at 2 months, R 2  = 0.36 and p  = 0.005 at 4 months), but this significance was lost by 6 months after HSCT. No correlation was seen between alemtuzumab levels and CD14/15 chimerism. Conclusion: Between 2 and 4 months after transplant, higher alemtuzumab levels measured 14 days after transplant correlated with patients having better engraftment, suggesting more lymphodepletion may be needed to reduce graft failure in these two non‐myeloablative matched related donor HSCT regimens.